Cognitive collaborations: sounding Southeast Asian sensibilities in Thai and Balinese rituals - Hood, Made Mantle; Binson, Bussakorn (International Association for Music & Medicine, 2014)
This article assesses the relationship between Thai and Balinese healing rituals focusing on music and indigenous explanatory models about emotional and cognitive processes. Emphasis is placed on how music and cognitive processes are conceptualised in both historical literature and contemporary interpretive frameworks in two geographically distinct areas of Southeast Asia. Both authors have spent decades observing rituals, performing music, and analysing musical structures. Yet there have been few opportunities to collaborate on a comparison of their findings. This essay will articulate how music is thought to have a direct physiological affect on its participants. The article first examines cross-cultural discourses in the literature that contain theoretical approaches to music and cognition. Then the article describes and compares Thai and Balinese healing rituals that address not only cognitive, but also corporeal and spiritual concepts that relate to broader Southeast Asian approaches to music and the mind.